Berberine Induces Autophagic Cell Death by Inactivating the Akt/mTOR Signaling Pathway - Park, Gil-Sun; Park, Bokyung; Lee, Mi-Young (Planta Medica, 2022)
The incidence of skin cancer has been increasing over the past decades, and melanoma is considered highly malignant because of its high rate of metastasis. Plant-derived berberine, an isoquinoline quaternary alkaloid, has been reported to possess multiple pharmacological effects against various types of cancer cells. Therefore, we treated melanoma B16F10 cells with berberine to induce cell death and understand the cell death mechanisms. The berberine-treated cells showed decreased cell viability, according to berberine concentration. However, western blot analysis of apoptosis-related marker proteins showed that the expression of Bcl-2, an apoptosis inhibitory protein, and the Bcl-2/Bax ratio were increased. Therefore, by adding 3-methyladenine to the berberine-treated cells, we investigated whether the reduced cell viability was due to autophagic cell death. The results showed that 3-methyladenine restored the cell viability decreased by berberine, suggesting autophagy. To clarify autophagic cell death, we performed transmission electron microscopy analysis, which revealed the presence of autophagosomes and autolysosomes in the cells after treatment with berberine. Next, by analyzing the expression of autophagy-related proteins, we found an increase in the levels of light chain 3A-II and Atg12-Atg5 complex in the berberine-treated cells. We then assessed the involvement of the Akt/mTOR signaling pathway and found that berberine inhibited the expression of phosphorylated Akt and mTOR. Our data demonstrated that berberine induces autophagic cell death by inactivating the Akt/mTOR signaling pathway in melanoma cells and that berberine can be used as a possible target for the development of anti-melanoma drugs.
Keywords: berberine; melanoma; autophagy; apoptosis